Phenotypic spectrum of children with nephronophthisis and related ciliopathies - König, Jens; Gretz, Norbert; Lablans, Martin (Clinical journal of the American Society of Nephrology, 2017)
Background and objectives: Genetic heterogeneity and phenotypic variability are major challenges in familial nephronophthisis and related ciliopathies. To date, mutations in 20 different genes (NPHP1 to -20) have been identified causing either isolated kidney disease or complex multiorgan disorders. In this study, we provide a comprehensive and detailed characterization of 152 children with a special focus on extrarenal organ involvement and the long-term development of ESRD. Design, setting, participants, & measurements: We established an online-based registry (www.nephreg.de) to assess the clinical course of patients with nephronophthisis and related ciliopathies on a yearly base. Cross-sectional and longitudinal data were collected. Mean observation time was 7.5±6.1 years. Results: In total, 51% of the children presented with isolated nephronophthisis, whereas the other 49% exhibited related ciliopathies. Monogenetic defects were identified in 97 of 152 patients, 89 affecting NPHP genes. Eight patients carried mutations in other genes related to cystic kidney diseases. A homozygous NPHP1 deletion was, by far, the most frequent genetic defect (n=60). We observed a high prevalence of extrarenal manifestations (23% [14 of 60] for the NPHP1 group and 66% [61 of 92] for children without NPHP1). A homozygous NPHP1 deletion not only led to juvenile nephronophthisis but also was able to present as a predominantly neurologic phenotype. However, irrespective of the initial clinical presentation, the kidney function of all patients carrying NPHP1 mutations declined rapidly between the ages of 8 and 16 years, with ESRD at a mean age of 11.4±2.4 years. In contrast within the non-NPHP1 group, there was no uniform pattern regarding the development of ESRD comprising patients with early onset and others preserving normal kidney function until adulthood. Conclusions: Mutations in NPHP genes cause a wide range of ciliopathies with multiorgan involvement and different clinical outcomes.
Gesehen am 10.10.2018